History of ice-rafting and water mass evolution at the northern Siberian Continental Margin (Laptev Sea) during Late Glacial and Holocene times - Taldenkova, Ekaterina; Bauch, Henning A.; Gottschalk, J.; Nikolaev, S.; Rostovtseva, Y.; Pogodina, I.; Ovsepyan, Y.; Kandiano, Evgeniya (Quaternary Science Reviews, 2010)
The Late Glacial and Holocene history of environmental changes in the western Laptev Sea is reconstructed on the basis of continuous records of ice-rafted debris (IRD) and Atlantic water indicative subpolar planktic foraminifers and benthic foraminifer Cassidulina neoteretis from the two AMS14C dated sediment cores, one from the upper continental slope and another from the Khatanga paleoriver valley on the outer shelf. Since seasonal sea ice cover is a permanent feature in this high Arctic region the prominent IRD-rich intervals in the oldest (>15.4 ka) and youngest (<7.2 ka) sediment units are attributed to iceberg-rafting. Rock types like phyllites are used as indicators of sediment material supplied by icebergs from local ice caps of the Severnaya Zemlya Archipelago. Authigenic concretions of vivianite and rhodochrosite found in the basal, IRD-rich core section on the slope, point to strong water stratification likely caused by meltwater inputs. The oldest Late Glacial IRD peaks provide evidence for iceberg production by the local ice caps on Severnaya Zemlya. Subsequent meltwater influence is tentatively related to the freshwater release from a retreating Barents–Kara ice sheet in the northeastern Kara Sea. Already prior to 15.4 ka Atlantic-derived waters intermittently reached the western Laptev Sea continental slope probably facilitated by upwelling in coastal polynyas. While subsurface Atlantic-derived waters were constantly present at the continental slope between 15.4 and 12 ka, the disappearance of C. neoteretis together with reduced abundance of subpolar planktic foraminifers after 12 ka suggests establishment of a freshened shelf water mass on the flooded outer shelf which affected the water mass structure on the continental slope. After 7 ka climate cooling and enhanced Atlantic-derived water inflow caused re-growth of ice caps on Severnaya Zemlya leading to a recurrence of IRD. Peaks of this renewed IRD input are centered at 7.2, 6.4, 5.4, 3, and 2 ka, implying that this millennial-scale ...